2019
DOI: 10.1146/annurev-vision-091718-014901
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Smooth Pursuit Eye Movements

Abstract: Smooth pursuit eye movements maintain the line of sight on smoothly moving targets. Although often studied as a response to sensory motion, pursuit anticipates changes in motion trajectories, thus reducing harmful consequences due to sensorimotor processing delays. Evidence for predictive pursuit includes ( a) anticipatory smooth eye movements (ASEM) in the direction of expected future target motion that can be evoked by perceptual cues or by memory for recent motion, ( b) pursuit during periods of target occl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 147 publications
2
44
0
Order By: Relevance
“…They rely on the integration of current motion information with priors based on experience across just a few trials or across a longer-term context (Darlington et al 2017; Deravet et al 2018; Yang et al 2012). Moreover, smooth pursuit can be triggered by the expectation of a certain motion direction even before the object’s motion onset, a phenomenon known as anticipatory smooth pursuit (Kowler et al 1984, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They rely on the integration of current motion information with priors based on experience across just a few trials or across a longer-term context (Darlington et al 2017; Deravet et al 2018; Yang et al 2012). Moreover, smooth pursuit can be triggered by the expectation of a certain motion direction even before the object’s motion onset, a phenomenon known as anticipatory smooth pursuit (Kowler et al 1984, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has revealed highly consistent effects of expectation on pursuit but contrasting effects on motion perception. For example, anticipatory pursuit can be triggered when observers repeatedly view stimuli moving into the same direction (Kowler 1989; Kowler et al 2019). The eyes are then attracted to the expected motion direction prior to the onset of the stimulus (attraction bias in direction).…”
Section: Introductionmentioning
confidence: 99%
“…First, its buildup is relatively fast, such that only a few trials are sufficient to observe the effects of specific regularities in the properties of visual motion, such as speed, timing or direction [10,44,46]. Second, it is a robust phenomenon, which has been observed on a large population of human participants and even in non-human primates (for a recent review see [47]). Note also, that human participants seem to be largely unaware of this behavior (as inferred from informal questioning).…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…We now test this idea on our population of FEF SEM neurons. A priori, such a mechanism could generalize to the smooth pursuit eye movement system, especially since humans and monkeys can initiate smooth pursuit in the absence of visual motion under certain conditions (Freyberg and Ilg, 2008; de Hemptinne et al, 2006; Kowler et al, 2019). Even if the output of FEF SEM truly is used as a gain signal, noise immunity might be enhanced if population activity resided in an output null state until there is a believable visual motion signal to drive pursuit initiation.…”
Section: Resultsmentioning
confidence: 99%